(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The central banks across the countries have attached increasing importance in recent decades to both monetary policy transparency and anchoring of private institutions expectations. Also, in the phase of COVID-19 related disruptions the role of RBI in India was swift. RBI is taking lots of efforts to accelerate the economic growth and control inflation. This research work aims at exploring the steps taken by Reserve Bank of India (RBI) in the direction of India’s goal of becoming a 5 trillion economy and finding out the change in monetary and fiscal rates to control inflation, promote growth and its impact on GDP and GVA. Research work also focuses on studying the instruments of monetary and fiscal policies used by RBI and understand different policy rates. This research work will attempt to study the various decisions and shift in policies done by RBI in order to normalizing the economic activities post pandemic. This work will also highlight the change in policy instruments and its immediate effect for the study period.